Is there a Judeo-Christian Tradition? A European Perspective - Nathan, Emmanuel; Topolski, Anya (Perspectives on Jewish Texts and Contexts, 2016)
The term ´Judeo-Christian` in reference to a tradition, heritage, ethic, civilization, faith etc. has been used in a wide variety of contexts with widely diverging meanings. Contrary to popular belief, the term was not coined in the United States in the middle of the 20th century but in 1831 in Germany by Ferdinand Christian Baur. By acknowledging and returning to this European perspective and context, the volume engages the historical, theological, philosophical and political dimensions of the term`s development. Scholars of European intellectual history will find this volume timely and relevant.